Symptoms, diagnosis and treatment of pancreatic cancer - Talar-Wojnarowska, Renata; Małecka-Panas, Ewa (Przewodnik Lekarza/Guide for GPs, 2007)
Pancreatic adenocarcinoma (PA) is characterized with very poor prognosis, being the fourth leading cause of adult death from cancer. The only effective process for complete cure depends on early detection and accurate surgical removal of the tumor. Unfortunately, most patients with pancreatic cancer show an advanced tumor at the time of diagnosis, due to either local progression or metastatic spread. Our review summarizes current aspects of PA epidemiology, clinical manifestations, treatment and the differential diagnosis, with emphasis on those factors that are of the most clinical importance.